Reducing trailing limb collisions in older adults through targeted leading limb placement after obstacle crossing: effect of closer foot placement - Tomoki Hakamata; Tomoki Hakamata; Takahiro Higuchi (Frontiers in Sports and Active Living)
IntroductionOlder adults experience a higher frequency of collisions with obstacles when stepping over obstacles, particularly with the trailing limb. We recently demonstrated that placing the leading limb closer to an obstacle after crossing effectively increases the toe height of the trailing limb, resulting in reduced collision. This study investigated whether the intervention of placing the leading limb closer to the obstacle is effective in reducing trailing limb collisions in healthy older adults.MethodsTwenty-one older individuals (11 males, 10 females; mean age 75.7 years) participated. Participants were allocated to one of two groups: a closer placement group, instructed to place the leading limb on a square target positioned on their walking path after crossing an obstacle, and a control group, instructed to cross the obstacle naturally. The target in the closer group was set at 0.5 times the leading limb's foot placement distance, as determined in a pre-test for each participant. The experimental design included a pre-test, intervention, and post-test.Results and discussionThe collision rate for the trailing limb in the closer group was significantly lower in the post-test than that in the pre-test. Furthermore, the variability in toe height and walking speed of the trailing limb in the closer group decreased significantly in the post-test compared to the pre-test. These findings suggest that the intervention of placing the leading limb foot closer to the obstacle after crossing may improve obstacle avoidance by the trailing limb in healthy older adults.